Cultures, clashes and peace - Erin Fletcher; Murat Iyigun (Institute for the Study of Labor (IZA), 2009)
Ethnic and religious fractionalization have important effects on economic growth and development, but their role in internal violent conflicts has been found to be negligible and statistically insignificant. These findings have been invoked in refutation of the Huntington hypothesis, according to which differences of ethnic, religious and cultural identities are the ultimate determinants of conflict. However, fractionalization in all its demographic forms is endogenous in the long run. In this paper, we empirically investigate the impact of violent conflicts on ethno-religious fractionalization. The data involve 953 conflicts that took place in 52 countries in Europe, Africa and the Middle East between 1400 CE and 1900 CE. Besides a variety of violent confrontations ranging from riots, revolts and power wars between secular sovereigns, the data cover religiously motivated confrontations. We document that countries in which Muslim on Christian wars unfolded more frequently are significantly more religiously homogenous today. In contrast, those places where Protestant versus Catholic confrontations occurred or Jewish pogroms took place are more fractionalized, both ethnically and religiously. And the longer were the duration of all such conflicts and violence, the less fractionalized countries are today. These results reveal that the demographic structure of countries in Europe, the Middle East and North Africa still bear the traces of a multitude of ecclesiastical and cultural clashes that occurred throughout the course of history. They also suggest that endogeneity could render the relationship between fractionalization and the propensity of internal conflict statistically insignificant. Finally, instrumenting for conflicts with some geographic attributes and accounting for the endogeneity of fractionalization with respect to ecclesiastical conflicts shows that religous fractionalization likely has negative effects on economic growth.
urn:nbn:de:101:1-20090513133
Keywords: C72; D74; N33; N43; O10; 330; Conflict; religion; institutions; economic development; Ethnische Diskriminierung; Religionsgemeinschaft; Bürgerkrieg; Politische Verfolgung; Entwicklung; Institutionalismus; Welt